Whistleblowing without borders: the risks and rewards of transnational whistleblowing networks - Hyde, Richard; Savage, Ashley (International Whistleblowing Research Network, 2015)
Cross-border disclosures by whistleblowers are of increasing importance. The regulatory regime is unclear, both with regard to employment protection and with regard to ensuring that the information reaches those able to best respond to the disclosure. This chapter considers the risks of cross-border disclosures, and how systems can change to accomodate them, so as to best achieve thier potential.